Optimalisasi Strategi Operasional “Safe Motherhood dan Childhood Survival” dengan Pendekatan Penilaian Status Gizi - Humairah Medina Liza Lubis; Bunail Isna Alfarisi; Tegar Alamsyah; Widya Yustika; Teuku Baihaqi Septiady; Aisyah Salsabila; Raihana Zavira; Rahmah Filzah; Annisa Rifqa Hestiana (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
Nutritional status is the state of the body due to food consumption and nutrient utilization that can be distinguished between poor, less, good, and more nutritional status which can have an impact on morbidity and mortality. An important factor in the incidence of infant morbidity and mortality is low birth weight due to the consumption of unhealthy foods during pregnancy and the period of supplementary feeding. This community service aims to determine the nutritional status of toddlers based on anthropometric measures. The service method is carried out through counseling, filling out questionnaires, and anthropometric measurements of infants aged < 1 year using scales and an infantometer. Assessment of children's nutritional status based on weight to height is severely wasted: <-3 SD, underweight: -3 SD to <-2 SD, normal: -2 SD to +1 SD, risk of overweight: >+1 SD to +2 SD, overweight: >+2 SD to +3 SD, and obesity: >+3 SD. The results of the service were obtained from 32 babies who were anthropometrically 24 children with normal status, 2 children were obese and 6 children were underweight.